Advice to the ruler in accordance with the provisions of Islamic Sharia (Eurasian Journal of Media and Communications, 2024)
Advice is one of the methods brought by the Great Qur’an and the purified Sunnah of the Prophet, because of its great importance in Islam ،as it is a direct discourse between the two parties, the ruler and the ruled, and between Muslims with each other ،with the aim of correcting the defect, correcting the crookedness, and reforming the human soul by pointing out the places of shortcomings and deviation in words and deeds.